Peran Fishway Pada Migrasi Ikan Air Tawar Dampak Dari Pembangunan Bendungan - Surya Dwi Palupi; Renata Tara Nurfitri; Rossa Cantika Putri; Rian Deca Pratama; Rajendra Rijal Sakhi; Rangga Juve Firmansyah; Ryan Pratama (Institut Teknologi Adhi Tama Surabaya, 2025)
Dams are structures that have been built by humans since thousands of years ago. A dam is a building or infrastructure designed to accommodate large water releases. The bigger a dam building, the more problems caused by the dam building infrastructure, one of which is the migration of freshwater fish. Indonesia currently has many dams built for infrastructure facilities, but there are still few dams that implement fishways. Increasingly large dam infrastructure can impede freshwater fish migration and cause a reduction in freshwater fish species and disrupt freshwater fish ecosystems. The structure of the river, which is lower downstream and higher upstream, causes significant changes in river flow patterns, resulting in changes in environmental conditions and also affecting the ecosystem. For this reason, the role of fishway construction is very important to help them get to their habitat and breed so as not to disturb the freshwater fish ecosystem. This article discusses the important role of fishway construction in the construction of dams, which cause obstacles to freshwater fish migration.